Effect of Preoperative Nasal Retainer on Nasal Growth in Patients with Bilateral Incomplete Cleft Lip: A 3-Year Follow-Up Study - Kim, Young Chul; Jeong, Woo Shik; Oh, Tae Suk; Choi, Jong Woo; Koh, Kyung S. (Archives of Plastic Surgery, 2017)
Background The purpose of this study was to evaluate changes in nasal growth after the implementation of a preoperative nasal retainer in patients with bilateral incomplete cleft lip.Methods Twenty-six infants with bilateral incomplete cleft lip and cleft palate were included in the study. A preoperative nasal retainer was applied in 5 patients from the time of birth to 2.6–3.5 months before primary cheiloplasty. Twenty-one patients who were treated without a preoperative nasal retainer were placed in the control group. Standard frontal, basal, and lateral view photographs were taken 3 weeks before cheiloplasty, immediately after cheiloplasty, and at the 1- and 3-year postoperative follow-up visits. The columella and nasal growth ratio and nasolabial angle were indirectly measured using photographic anthropometry.Results The ratio of columella length to nasal tip protrusion significantly increased after the implementation of a preoperative nasal retainer compared to the control group for up to 3 years postoperatively (P<0.01 for all time points). The ratios of nasal width to facial width, nasal width to intercanthal distance, columellar width to nasal width, and the nasolabial angle, for the two groups were not significantly different at any time point.Conclusions Implementation of a preoperative nasal retainer provided significant advantages for achieving columellar elongation for up to 3 years postoperatively. It is a simple, reasonable option for correcting nostril shape, preventing deformities, and guiding development of facial structures.
Keywords: Nose; Anthropometry; Cleft lip